Effects of an 8-Week Intervention Targeting the Veridicality of Actual and Perceived Motor Competence Among Irish Adolescents in Project FLAME. Issue 5 (October 2021) - Philpott, Conor; Utesch, Till; Belton, Sarahjane; Donovan, Brian; Chambers, Fiona; Lester, Diarmuid; O'Brien, Wesley
High levels of perceived motor competence and low levels of actual motor competence in youth populations have been reported world-wide. Both perceived and actual motor competence have been deemed independent correlates of health and physical activity (PA) behavior, and past research has indicated that their alignment may be linked to more consistent PA. Moreover, there is potential for a movement-based intervention to strengthen the alignment between perceived and actual motor competence, perhaps then guiding future health, PA, and community sport engagement globally. Thus, the objective of this study was to investigate the effectiveness of an 8-week movement-based intervention on increasing the alignment (i.e., veridicality) between PMC and AMC among Irish adolescent youth. We collected data on adolescents ( n = 324; females = 149; M age = 14.5, SD = 0.88 years) across six second-level schools in Ireland, including measurements of actual and perceived, motor competence at pre- and post-intervention. We observed low levels of actual in contrast to high levels of perceived motor competence. We found a small but significant veridical alignment between perceived and actual motor competence, but there was no intervention effect on alignment. Future research should prioritize a longer intervention duration that targets student learning and understanding in order to develop veridical perceptions in adolescents that might sustain their participation in PA.